2011
DOI: 10.1063/1.3671861
|View full text |Cite
|
Sign up to set email alerts
|

On electric fields created by quantized vortices

Abstract: It is shown that in a magnetic field quantized vortices in a superfluid obtain a real quantized electric charge concentrated in the vortex core. This charge is compensated by an opposite surface charge located at a macroscopic distance from the vortex axis. It is determined that the polarization caused by the vortex velocity field does not give rise to electric fields outside an infinite cylinder. Observation of electric fields created by the vortices is possible only near the end surfaces of the cylinder whic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…We see a fundamental difference of the expressions (28) and (29) from the similar expressions (21) in the previous section. Because of this difference, in this case the system energy E ¼ h0jĤj0i is a functional in the form of an infinite series in powers of U and U þ .…”
Section: A Coherent State Of Fermion Pairsmentioning
confidence: 69%
See 3 more Smart Citations
“…We see a fundamental difference of the expressions (28) and (29) from the similar expressions (21) in the previous section. Because of this difference, in this case the system energy E ¼ h0jĤj0i is a functional in the form of an infinite series in powers of U and U þ .…”
Section: A Coherent State Of Fermion Pairsmentioning
confidence: 69%
“…2 and 17) and in terms of the two-particle order parameter U(r 1 , r 2 ). [18][19][20][21] It is found that there are fundamental differences between these two approaches. In applying the first method to composite bosons the effects related to the exchange interaction are completely lost, which in some cases, particularly in the case of the Coulomb interaction between the particles, leads to qualitatively incorrect results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations